(untitled) (Revista Brasileira Multidisciplinar, 2013)
Related researches for the treatment of skin wounds is a matter of interest to researchers seeking new products and technology with the possibility of accelerating the healing process. The present study had as aim to analyze the healing action of "Barbatimão" ointment at 5% (Stryphnodendrom Barbatiman Martius) associated with low intensity pulsed ultrasound on the second intention healing process. The experiment was carried out using 24 Wistar rats (250-300g) divided into 4 groups: A was the control group, B: was treated with Barbatiman ointment, C: with pulsating ultrasound and D: with a combination of pulsating ultrasound and Barbatiman ointment. After anaesthesia with Ketamin 100g/kg and Xilamin chlorohidrate 6mg/kg, the dorsal region of the animal was shaved and an approximate 1.0 cm2 incision into the subcutaneous tissue was made. It was seen that in the first 5 days of treatment (p=0,1) the pulsating Ultrasound presented the best healing when compared to the "Barbatimão" ointment (p=0.2). However, after 10 days the lesions treated with "Barbatimão" showed that this treatment was better (p=0.3) compared to the pulsating ultrasound (p=0.9), but the association of the two types of treatments was not as successful at accelerating the healing process. Thus it was determined that separately they were more efficient at healing wounds.